Higher alcohol–biodiesel–diesel blends: An approach for improving the performance, emission, and combustion of a light-duty diesel engine. (1st March 2016) - Imdadul, H.K.; Masjuki, H.H.; Kalam, M.A.; Zulkifli, N.W.M.; Alabdulkarem, Abdullah; Rashed, M.M.; Teoh, Y.H.; How, H.G.
Highlights: The fuel properties of higher alcohol blended biodiesel were improved. Higher alcohol shows remarkable increase in the BP, BTE and decrease the BSFC. Alcohols mixed with biodiesel diminishes HC, CO and smoke significantly. CO2 emissions of pentanol blended fuel decreases at maximum speed. Higher alcohol blended biodiesel showed improved combustion. Abstract: Pentanol is a long-chain alcohol with five carbons in its molecular structure and is produced from renewable feedstock, which may help to improve the challenging problems of energy security and environmental issues. In this investigation, the performance, emission, and combustion characteristics of a single-cylinder, four-stroke, water-cooled, direct-injection diesel engine were evaluated by using 10%, 15%, and 20% pentanol and Calophyllum inophyllum (CI) biodiesel blends in diesel under different speed conditions. The fuel properties of the blended fuels were measured and compared. Combustion attributes, such as cylinder pressure and heat-release rate, were also analyzed. Results indicated that increasing the proportion of pentanol in biodiesel blends improved the fuel properties compared with 20% blend of CI biodiesel (CI 20). The modified blends of pentanol showed reduced brake-specific fuel consumption with higher brake thermal efficiency and brake power than CI 20. Although the modified test blends showed a slightly higher nitric oxide emission, the carbon monoxide emission and unburned hydrocarbon emission for 15% and 20% blends of pentanol showed even better reduction than CI 20. Smoke emission was also reduced significantly. The carbon dioxide emission of the test blends were reduced at the maximum speed condition compared to CI 20. In terms of combustion, the modified test fuels exhibited a significant improvement, thus indicating better performance and emission. This study concluded that the 15% and 20% blends of biodiesel, diesel, and pentanol can optimize engine performance and emission without any engine modification.